What mental health professionals in Israel know and think about adolescent problem gambling. Issue 1 (2nd January 2016) - Sansanwal, Rayna M.; Derevensky, Jeffrey L.; Gavriel-Fried, Belle
Abstract: Mental health professionals are well versed in addressing multiple adolescent risky behaviours and play a primary role in the identification of and referral process and service provision for young people who engage in such behaviours. Given their 'person-in-environment' approach, training in multi-sectoral collaboration, and awareness of social policies, social workers are especially equipped to provide needed mental health services to young people. The aim of the current study was to examine Israeli mental health professionals' awareness of and attitudes towards adolescent high-risk behaviours, including gambling. Child psychologists, social workers and school counsellors ( N = 273) completed an online survey addressing concerns related to high-risk behaviours. Findings revealed that social workers perceived gambling as being among one of the least concerning adolescent mental health issues and reported feeling the least confident in their abilities to provide services to young people with gambling problems. The results suggest the importance of youth gambling addictions being incorporated into social work training curricula.